From the National Housing Bank to the My Home My Life program: Reproducing old obstacles in the housing policy in Aracaju-SE, Brazil - Alves Franca, Sarah Lucia; Rezende, Vera Lucia F. (International Planning History Society Proceedings, 2018)
This article comparatively analyzes the policies of the National Housing Bank – BNH, and the Habitation Program entitled My Home My Life, based on the locational logic of subsidized housing complexes in the city of Aracaju-SE, Brazil. In Brazil, two programs deserve special mention: BNH, created in 1964 as the financing body for the construction of social housing, producing thousands of housing units until 2002, opening up expansion fronts for the reproduction of the real estate market. In the second, the PMCMV, initiated in 2009, one of the biggest obstacles is access to urbanized land, with alternative to the occupation of scattered, devalued and deprived areas of environmental sanitation and public transportation. So, it is questioned to what extent the actions of the PMCMV, regarding the dynamics of housing production resemble or are distinguished from those undertaken by BNH? For the development of this, quantitative and qualitative information was collected in public agencies, generating tables and mapping the insertion of the enterprises in Aracaju. Thus, there are coincidences regarding the peripheral and dispersed logic of these sets, highlighting the clear socio-spatial segregation of the lower income strata, in the search for land valuation in function of public and private investments.